2021
DOI: 10.3389/fvets.2021.757136
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Feed Protocol in a Mouse Model That Mimics Marasmic Malnutrition

Abstract: Host nutritional status directly interferes with immunity and/or susceptibility to infectious diseases. To understand the mechanisms behind this relationship, the use of animal models and feeding protocols is necessary. In the literature, studies reporting marasmic malnutrition in mice are not common. In this context, the objective of this study was to validate a feed methodology that mimics marasmic malnutrition, examining the nutritional, biochemical, and hematological status in BALB/c mice. Weaned BALB/c mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…While this results in a severe phenotype regarding growth and weight, our mice did not show any particular sign of torpor, reduced activity, or change in appetite during the nutritional challenge. Moreover, unlike Ferreira-Paes et al (21), who describe a model of marasmus using weanling BALB/c mice, nutritional rehabilitation in male mice did not fully resolve the severity of protein malnutrition. Indeed, in our experimental setting, male mice were stunted after nutritional rehabilitation, although early-life wasting was corrected.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…While this results in a severe phenotype regarding growth and weight, our mice did not show any particular sign of torpor, reduced activity, or change in appetite during the nutritional challenge. Moreover, unlike Ferreira-Paes et al (21), who describe a model of marasmus using weanling BALB/c mice, nutritional rehabilitation in male mice did not fully resolve the severity of protein malnutrition. Indeed, in our experimental setting, male mice were stunted after nutritional rehabilitation, although early-life wasting was corrected.…”
Section: Discussionmentioning
confidence: 70%
“…However, it does not exhibit classic traits of kwashiorkor such as edema and hepatomegaly (31), probably due to the fact that our mice are not in contact with any enteric pathogens and thus are not susceptible to infection and inflammation. Indeed, several studies have shown that malnourished mice are more susceptible to infection, thus mimicking one of the hallmarks of human malnutrition (20,21). Furthermore, nutritional rehabilitation after kwashiorkor results in increased IGF-1 levels, but the values are lower than in healthy children (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the clinical scenario, impaired liver function leads to altered biochemical parameters in marasmus protein malnutrition. 19 Literature also indicates that the increase in Kupffer cells results from malnutrition. 36 Considering this evidence, our study confirms that the developed mice model is stable and clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Recently, a study using a low protein diet (LPD) was validated. 19 The validated diet was used for a concise period of observation and would not resemble the clinical condition where the exposure is chronic/ continuous.…”
Section: Introductionmentioning
confidence: 99%